Evaluation of Implementing Information Technology Risk Governance Based on COSO ERM at PT. ABC - Matias Andika Yuwono; Lena Ellitan (Jurusan Sistem Informasi Fakultas Ilmu Komputer Universitas Sriwijaya, 2026)
In this digital era, where every organization relies heavily on information technology (IT) for daily operations, ensuring good IT risk management through Information Technology Risk Governance (ITRG) becomes crucial. The risks emerging from this dependency are diverse and complex, ranging from cybersecurity threats to IT system failures to data breaches, which can cause significant financial loss and reputation damage. Effective implementation of ITRG protects the company from these risks and enhances the quality of information produced for decision-making. With these various issues, PT. ABC also aims to enhance the company's value in terms of data security, effective data processing, and producing relevant reports for the company's leaders. PT. ABC conducts an ITRG evaluation in the IT division using a triangulation approach involving interviews with IT managers, which financial and internal audit managers confirm. This step aims to ensure effective ITRG implementation in the IT division. The ITRG assessment of the IT division is based on the governance and culture component of the Committee of Sponsoring Organizations of the Treadway Commission (COSO) Enterprise Risk Management (ERM), which includes five main principles: risk supervision, operational structure, desired culture, commitment to core values, and attracting, developing, and retaining competent individuals. The research results indicate that the IT division of PT. ABC has effectively implemented these five principles, thus PT. ABC has successfully applied ITRG, hoping to provide adequate data information services to relevant stakeholders.